Criminal Justice and Juvenile Offenders - Vileikienė, Eglė (Sociologija. Mintis ir veiksmas, 2015)
The aim of the article is to discuss the relationship between juvenile offenders and system of criminal justice. The author takes her point of departure in an overview of the different ways of interpreting the deviant behaviour. The author argues for an understanding of juvenile offense as form social action that cannot be understood without the contextual sociological analysis and questions the possibility of crime prevention by means criminal justice alone.
Keywords: criminal offense; juvenile; criminal justice